Large-scale fabrication of free-standing and sub-μm PDMS through-hole membranes. Issue 16 (16th April 2018) - Le-The, Hai; Tibbe, Martijn; Loessberg-Zahl, Joshua; Palma do Carmo, Marciano; van der Helm, Marinke; Bomer, Johan; van den Berg, Albert; Leferink, Anne; Segerink, Loes; Eijkel, Jan
Abstract : A robust and simple method was developed for large-scale fabrication of free-standing and sub-μm PDMS through-hole membranes for biomedical applications. Abstract : Free-standing polydimethylsiloxane (PDMS) through-hole membranes have been studied extensively in recent years for chemical and biomedical applications. However, robust fabrication of such membranes with sub-μm through-holes, and at a sub-μm thickness over large areas is challenging. In this paper, we report a robust and simple method for large-scale fabrication of free-standing and sub-μm PDMS through-hole membranes, combining soft-lithography with reactive plasma etching techniques. First, arrays of sub-μm photoresist (PR) columns were patterned on another spin-coated sacrificial PR layer, using conventional photolithography processes. Subsequently, a solution of PDMS : hexane at a 1 : 10 ratio was spin-coated over these fabricated arrays. The cured PDMS membrane was etched in a plasma mixture of sulfur hexafluoride (SF6 ) and oxygen (O2 ) to open the through-holes. This PDMS membrane can be smoothly released with a supporting ring by completely dissolving the sacrificial PR structures in acetone. Using this fabrication method, we demonstrated the fabrication of free-standing PDMS membranes at various sub-μm thicknesses down to 600 ± 20 nm, and nanometer-sized through-hole (810 ± 20 nm diameter) densities, over areas as large as 3 cm in diameter. Furthermore, we demonstrated the potential of the as-prepared membranes as cell-culture substrates for biomedical applications by culturing endothelial cells on these membranes in a Transwell-like set-up.